(untitled) (Altre Modernità, 2019)
This article investigates the conquests of the utopian and the current spaces of possibility. This multiprospective exploration is composed of three movements: ideas, practices, and symbols. The first part considers the concepts of utopianism, from its origins and developments in literature, to the principles recurring in ideal worlds. The second part concerns the practices of the utopian, from historical incarnations to current examples of effective realizations – including some “minimalist” daily practices – based on ethnographic experiences in intentional communities, autonomous regions, and informal settlements. The third part examines the symbols of the conquest of the utopian. The occupations of forests in different geographical areas (including the Hambacher Forst) introduce scenarios opened by the recent mobilizations against the climate crisis. The interrelationship between ideas, practices, and symbols are the subject of theoretical reflections, which come from classical literature to the latest contributions on communitarianism and grassroot movements.